Efeito alelopático de sabugueiro e capim-limão na germinação de picão-preto e soja - Fortes, Andréa Maria Teixeira; Mauli, Márcia Maria; Rosa, Danielle Medina; Piccolo, Gislaine; Marques, Denise Sommer [UNESP]; Refosco, Rachel Mohana de Carvalho (Editora da Universidade Estadual de Maringá (EDUEM), 2009)
As plantas invasoras são constantes e diminuem a produtividade das culturas por competirem por espaço, nutrientes e água. Dessa forma, os agricultores adotam, em grande escala, produtos químicos eficientes no controle da lavoura e com alta toxicidade ao meio ambiente. Existem, no entanto, formas alternativas para o controle de invasoras, por meio de aleloquímicos presentes em algumas plantas, dentre elas, as medicinais. Este trabalho tem como objetivo analisar as propriedades alelopáticas dos extratos das plantas medicinais Cymbopogon citratus (DC) Stapf. e Sambucus australis Cham. and Schltdl. em inibir a germinação de Bidens pilosa L., sem interferir na germinação de Glycine max L. Merrill. Os extratos foram obtidos triturando-se 200 g de folhas com 1 L de água destilada. As sementes foram mantidas em B.O.D. à temperatura de 25ºC, com fotoperíodo de 12h de luz. Nas condições em que foram realizados os experimentos, constatou-se que o extrato de capim-limão inibiu a germinação de picão-preto sem que este inibisse a germinação da soja, enquanto o extrato de sabugueiro inibiu a germinação de picão-preto e a germinação da soja. Assim, indica-se a utilização do capim-limão, como um herbicida natural para o picão-preto.

Agriculture has been suffering adaptations throughout time, from hard hand labor to the most advanced sowing and harvesting techniques. Invasive plants are a constant, diminishing productivity by competing for space, nutrients, and water. Therefore, farmers have adopted, on a large scale, the use of efficient synthetic chemicals, which are highly toxic to the environment, in order to control plant production. However, there are other alternative means to control those competitors: using allelochemicals present in some plants, such as medicinal ones. The objective of this paper is to analyze allelophatic properties of the medicinal plants Cymbopogon citratus (DC) Stapf. and Sambucus australis Cham. and Schltdl., and inhibit Bidens pilosa L. without interfering on Glycine max L. Merrill germination. The extracts were obtained by crushing 200 g of leaves and mixing them with 1 liter of distilled water. The seeds were kept in B.O.D. at a temperature of 25ºC, with a photoperiod of 12 hours of light. Considering the conditions in which the experiment was performed, it was concluded that the warm liquid extract of Cymbopogon citratus restrained the germination of Bidens pilosa L. without interfering on the germination of soybean, whereas the warm liquid extract of Sambucus australis Cham. constrained soybean and Bidens pilosa L. germination. Thus, the use of Cymbopogon citratus (DC) Stapf. as a natural herbicide for Bidens pilosa L. is recommended.
Allelophatic effect of Sambucus australis Cham. and Schltdl. and Cymbopogon citratus (DC) Stapf. in the germination of Bidens pilosa L. and soybeans
Keywords: alelopatia; espécies invasoras; agricultura; allelopathy; invasive specie; agriculture